COMPARATIVE ANALYSIS OF SERBIAN AGRICULTURE AND AGRICULTURE OF OTHER HIGH MIDDLE-INCOME COUNTRIES - Andjelković, Tiana; Janković-Milić, Vesna; Lepojević, Vinko; Jovanović, Sonja (Economics of Agriculture, 2024)
The goal of countries that have excellent comparative advantages for the development of agriculture, such as Serbia, is rural development and the general development of agriculture as an economic branch. This is logical, given the great importance of food available to everyone. According to the World Bank classification, Serbia belongs to the group of countries with high middle income. The aim of this paper is to present the impact of the economic development of the observed countries on the production of food. Methodologies applied for this research are: single correlation and single and multiple regression models and indicators such as global food security index, gross domestic product per capita, share of agriculture in gross domestic product for the year 2022 will be used.